The value of motherhood and psychological distress among infertile women: The mediating role of coping strategies - Florentina Larisa Foti; Adina Karner-Huţuleac; Alexandra Maftei (Frontiers Media S.A., 2023)
IntroductionThe present study investigated psychological distress and coping strategies among infertile women during the COVID-19 pandemic using a multi-dimensional model of infertility-related stress. We explored the associations between individual (i.e., age) and situational characteristics related to infertility (i.e., duration of infertility, cause of infertility, number of lost pregnancies, and assisted reproductive techniques [ART] status), and perceived-infertility-related factors (i.e., the perceived importance of motherhood).MethodsOur total sample consisted of 193 women aged 20 to 46 (M= 33.23, SD = 4.58), out of which 102 were undergoing ART procedures (M = 33.60, SD = 4.23), and 91 were not (M= 32.81, SD = 4.94). Participants filled in questionnaires measuring psychological distress, coping strategies, and the importance of motherhood.ResultsCorrelation analyses suggested that the importance of motherhood was positively associated with psychological distress and negative coping strategies. Mediation analysis results indicated that both in the overall sample and in the sample of women undergoing ART procedures, the negative self-perception fully mediated the link between the importance of motherhood on psychological distress. In the non-ART sample, we found a significant mediation effect of denial on the link between the importance of motherhood and psychological distress.DiscussionWe discuss the theoretical and practical implications of the present findings, focusing on the mental health-related consequences of the social stigma of infertility heightened by the pressure of parenthood.